Case reportPyoderma gangrenosum in the head location: a clinical study of three cases - Barańska-Rybak, Wioletta; Komorowska, Olivia; Szczerkowska-Dobosz, Aneta; Nowicki, Roman; Roszkiewicz, Jadwiga (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Pyoderma gangrenosum is a rare disorder whose aetiopathology is still unknown. The clinical manifestation of the disease is the presence of extensive ulcerations. Skin lesions can occur in several locations – on the trunk, on the limbs and also rarely in the skin of genitourinary organs. We present three cases of pyoderma gangrenosum in the rare head localization with diagnostic and therapeutic difficulties associated with this disorder.